2014
DOI: 10.1371/journal.pone.0106048
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inducible Nitric Oxide Synthase (iNOS) in Microglia of the Developing Quail Retina

Abstract: Inducible nitric oxide synthase (iNOS), which produce large amounts of nitric oxide (NO), is induced in macrophages and microglia in response to inflammatory mediators such as LPS and cytokines. Although iNOS is mainly expressed by microglia that become activated in different pathological and experimental situations, it was recently reported that undifferentiated amoeboid microglia can also express iNOS during normal development. The aim of this study was to investigate the pattern of iNOS expression in microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 103 publications
(148 reference statements)
6
58
0
Order By: Relevance
“…iNOS is expressed in multiple cell types, such as macrophages (Lumeng et al 2007), plasma cells (Fritz et al 2012), epithelia cells (Kolios et al 1998) and microglia cells (Sierra et al 2014), and is probably signalling from multiple sources in the present study. A number of studies have revealed that a high-fat diet increases NO production or iNOS expression in many different sites, such as plasma (Stanimirovic et al 2016), liver (Feng et al 2016), kidney (Sherif, 2014), small intestine (Ou et al 2012) and adipose tissue (Perreault & Marette, 2001), although not all studies have identified an increase (Perreault & Marette, 2001;Eccleston et al 2011;Stanimirovic et al 2016).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…iNOS is expressed in multiple cell types, such as macrophages (Lumeng et al 2007), plasma cells (Fritz et al 2012), epithelia cells (Kolios et al 1998) and microglia cells (Sierra et al 2014), and is probably signalling from multiple sources in the present study. A number of studies have revealed that a high-fat diet increases NO production or iNOS expression in many different sites, such as plasma (Stanimirovic et al 2016), liver (Feng et al 2016), kidney (Sherif, 2014), small intestine (Ou et al 2012) and adipose tissue (Perreault & Marette, 2001), although not all studies have identified an increase (Perreault & Marette, 2001;Eccleston et al 2011;Stanimirovic et al 2016).…”
Section: Discussionsupporting
confidence: 48%
“…) and microglia cells (Sierra et al . ), and is probably signalling from multiple sources in the present study. A number of studies have revealed that a high‐fat diet increases NO production or iNOS expression in many different sites, such as plasma (Stanimirovic et al .…”
Section: Discussionmentioning
confidence: 99%
“…They were blocked for 15 minutes in PBS-Tr containing 5% normal goat serum (NGS) at room temperature and incubated overnight at 4°C in a mix of monoclonal anti-BrdU (1:800) (Sigma) and polyclonal anti-iNOS (1:500) (Abcam, Cambridge, United Kingdom) antibodies, both diluted in BSA-PBS-Tr. Polyclonal anti-iNOS antibody was used as microglial marker, because amoeboid microglia express iNOS during the normal embryonic development of quail retina [ 20 ]. The explants were subsequently rinsed in PBS-Tr and incubated with the secondary antibodies Alexa Fluor 594-conjugated goat anti-mouse IgG and Alexa Fluor 488-conjugated goat anti-rabbit IgGs for 2 hours at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent radial migration in a vitreal-to-scleral direction allows amoeboid microglia to reach the plexiform layers, where they differentiate into ramified microglia. Other studies in our lab showed that in vitro cultures of quail embryo retina explants mimic the migration and differentiation of microglial precursors in the in situ developing retina [ 19 , 20 ]. Therefore, these organotypic cultures of retina explants represent an excellent experimental model system to investigate possible molecular factors involved in the entry of microglial precursors into the retina.…”
Section: Introductionmentioning
confidence: 99%
“…species, prostaglandins, NO, cyclooxygenase-2, adenosine and a range of other inflammatory and signalling molecules [73,74]. Experimental evidence gleaned from healthy human volunteers involving intravenous administration of inflammatory mediators such as lipopolysaccharides (LPS) revealed a significant reduction in the duration of REM sleep and a significant increase in the duration NREM sleep [75,76].…”
Section: Peripheral Inflammation As a Mechanism Of Impaired Sleep Hommentioning
confidence: 99%